Estimation of the consumption in Iraq using the method of cointegration - Ibrahim J. Kadom; Haithem Y. Yousif; Hisham F. Abd Al-lateef (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The research contains two parts, theoretic& practice. The theoretical show hypothesis and aims of the research, which is testing of income and consumption time series stability in Iraq at (1986-2006) has co-integration by using a correct model. The research problem is how to testing the income time series function stability and how to resolve spurious regression of the model estimation, in this part is analyzing of independent variable (Income). The concept of time series and its stability, the autocorrelation function and its specification and the concept of co-integration mathematical function. In the practical parts the research indicate that (%64.4) of the consumption changes is explained by the income, (%35.6) is explained by the external variables within random variables The important conclusion indicate that is necessary to testing the time series integration before any estimating if we don’t want to fail in the spurious regression problems.